Exploring plant responses to abiotic stress by contrasting spectral signature changes - Estrada, Félix; Flexas, Jaume; Araus, Jose Luis; Mora-Poblete, Freddy; Gonzalez-Talice, Jaime; Castillo, Dalma; Matus, Ivan A.; Méndez-Espinoza, Ana Maria; Garriga, Miguel; Araya-Riquelme, Carlos; Douthe, Cyril; Castillo, Benjamin; et al. (Frontiers in Plant Science, 2023)
In this study, daily changes over a short period and diurnal progression of spectral reflectance at the leaf level were used to identify spring wheat genotypes (Triticum aestivum L.) susceptible to adverse conditions. Four genotypes were grown in pots experiments under semi-controlled conditions in Chile and Spain. Three treatments were applied: i) control (C), ii) water stress (WS), and iii) combined water and heat shock (WS+T). Spectral reflectance, gas exchange and chlorophyll fluorescence measurements were performed on flag leaves for three consecutive days at anthesis. High canopy temperature (HCT) genotypes showed less variability in their mean spectral reflectance signature and chlorophyll fluorescence, which was related to weaker responses to environmental fluctuations. While low canopy temperature (LCT) genotypes showed greater variability. The genotypes spectral signature changes, in accordance with environmental fluctuation, were associated with variations in their stomatal conductance under both stress conditions (WS and WS+T); LCT genotypes showed an anisohydric response compared that of HCT, which was isohydric. This approach could be used in breeding programs for screening a large number of genotypes through proximal or remote sensing tools and be a novel but simple way to identify groups of genotypes with contrasting performances.